Pengaruh Keunggulan Bersaing, Orientasi Pasar, Inovasi, terhadap Kepuasan Pelanggan - Putri Dwi Cahyani; Elva Syanistya Nur K; Imas Laili Nur’aini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Increasingly competitive competition in the business world makes a business faced with opportunities and threats. MSEs in the combongan village must be able to compete and maintain their business in the midst of the tight business world by understanding the desires of their customers. The purpose of this study was to determine the effect of innovation, competitive advantage, and market orientation on customer satisfaction at MSEs in Combongan hamlet. The research population is consumers who shop at the UMK in Combongan hamlet. The technique used is purposive sampling by distributing questionnaires which are measured by a Likert scale. Multiple regression analysis is an analytical technique used in this study. The results of this study indicate that innovation has no effect on customer satisfaction, competitive advantage has a positive effect on customer satisfaction and market orientation has no effect on customer satisfaction. The results of this study also show that simultaneously the variables of innovation, competitive advantage, and market orientation have a positive effect on customer satisfaction at MSEs in Combongan village. Keywords: innovation; competitive advantage; market orientation; customer satisfaction